Unbound: Analyzing White Supremacy in American Literature, 1892-1903 - Scully, Jessica. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of English.; Advisor: Elizabeth Ammons.; Committee: Nathan Wolff, Modhumita Roy, and Nadine Knight.; Keywords: American literature, and Literature.